Implications of Network Structure on Small Firms' Performance: Evidence from Italy - Michele Rubino; Filippo Vitolla (International Journal of Business and Management, 2018)
The aim of this paper is to examine whether and how some structural characteristics of the Italian Network contract (NC) influence small firms' performance. Since the '70s Italy has had a long history of network alliances characterized by the establishment of the industrial districts. However, this type of informal agreements have proved to be inadequate to counter the effects of globalization and of the changes that have occured in the international economic scenario. Consequently, the legislator has enacted the law n. 33/2009 by introducing a new type of formal agreement, named NC, in order to increase firms' competitiveness. Research findings on the Italian NC have shown the existence of positive effects on firms' performance. However, in most cases the analyses have been based on a limited number of firms and have not verified the influence of some network structural characteristics. This research wishes to fill this gap by increasing the existing literature on the subject. The empirical analysis, based on a firm level panel data, highlights that in networks composed of small firms the results are not always consistent with prior studies. Network characteristics differently influence the firms' performance measures. The analysis shows that network diversity and network's geographical openness are negatively related to firms' performance. Instead, network size has a limited impact on firms' performance expressed only by the ROA.
Keywords: 330; Network agreements; Network diversity; Network's geographical openness; Network size; Small firms' performance; Italian SMEs